2012
DOI: 10.1095/biolreprod.111.095984
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedin B and Its Receptor Influence the Activity of Myometrial Primary Cells In Vitro Through Regulation of Il6 Expression via the Rela/p65 Pathway in Mice1

Abstract: The neuromedin B receptor (Nmbr) is an important physiological regulator of spontaneous activities and stress responses through different cascades as well as its autocrine and paracrine effects. Previous studies have revealed that neuromedin B (Nmb) and its receptor signal via the Rela (also known as p65)/Il6 pathway in a mouse model of pregnancy. This study investigated the mechanism of Nmbr signaling via the Rela/p65-Il6 pathway and regulation of the concentration of intracellular free calcium ([Ca(2+)](i)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…While research regarding its impact on fetal loss is limited, Zhang and colleagues (2012) investigated Nmb and its receptor's (Nmbr) roles in pre-term pregnancies in mice. The authors suggested that the interaction between Nmb/Nmbr may influence myometrial cells via the Rela/p65 pathway [99]. The Rela/p65 pathway is an important upstream regulator of the labor-induced processes involving uterine smooth muscle through regulation of phospholipase C/protein kinase C, myosin light-chain phosphorylation, and free intracellular calcium [99,100].…”
Section: Master Regulators Shared In Two or More Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While research regarding its impact on fetal loss is limited, Zhang and colleagues (2012) investigated Nmb and its receptor's (Nmbr) roles in pre-term pregnancies in mice. The authors suggested that the interaction between Nmb/Nmbr may influence myometrial cells via the Rela/p65 pathway [99]. The Rela/p65 pathway is an important upstream regulator of the labor-induced processes involving uterine smooth muscle through regulation of phospholipase C/protein kinase C, myosin light-chain phosphorylation, and free intracellular calcium [99,100].…”
Section: Master Regulators Shared In Two or More Populationsmentioning
confidence: 99%
“…The authors suggested that the interaction between Nmb/Nmbr may influence myometrial cells via the Rela/p65 pathway [99]. The Rela/p65 pathway is an important upstream regulator of the labor-induced processes involving uterine smooth muscle through regulation of phospholipase C/protein kinase C, myosin light-chain phosphorylation, and free intracellular calcium [99,100]. Mutations or dysregulation of this NMB may induce an SA or pre-term birth due to its involvement in regulating genes involved in calcium cascades (NCLAD, CAMK2G, PLCB1, PRKCB) and its previous association with uterine smooth muscle contractions [97,99].…”
Section: Master Regulators Shared In Two or More Populationsmentioning
confidence: 99%
“…Primary cell cultures have been shown to retain morphological and functional characteristics and expression of NMBR were shown to be retained for at least 4 generations. [ 9 ] This study explored the interactions between NF-κB and AP-1 and their intracellular localization changes the first time in the USMCs to discover the underlying mechanism of labor onset, by using HLPMCs before or after labor onset in vivo and primary culture HLPMCs in vitro. Standard immunochemical staining techniques were used to demonstrate positive expression of a-SMA and NMBR in the primary culture of myometrial cells, thus confirming the myogenic origin of cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that NMB and its receptor can induce labor onset in pregnant mice and influence the activity of myometrial primary cells in vitro via a RELA (NF-κBp65)/IL6-mediated pathway. [ 8 , 9 ] Those findings strongly indicated that NMB binding to NMBR can activate both NF-κB and AP-1 pathways to induce labor initiation, and some interactions between NF-κB and AP-1 may exist to play a synergistic role in the process of parturition initiation. The present study proposed to use co-immunoprecipitation (CO-IP), western blotting, immunohistochemistry (IHC), and immunocytofluorescence (ICF) techniques to explore their interaction and intracellular localization changes in the myometrial cells in vivo and in vitro to discover the underlying mechanism of labor onset.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation